STUDY OF EQUIVALENCE EDUCATION PROGRAM STUDENTS’ SOFT SKILLS LEVEL IN PREPARING TO ENTER THE COMPETITIVE DIGITAL AGE JOB MARKET - Elis Taryamah (Kopertis Region IV Jabar and Banten, 2022)
Soft skills are critical for learners at Al Ghofur Community Learning Center to develop in order to equip them with the knowledge, attitude, mentality, and abilities necessary to compete and succeed in the labor market. The purpose of this research is to offer an overview of the mastery of soft skills achieved by students enrolled in the B and C Package Equivalence Education Program at Al Ghofur Community Learning Center as they prepare to enter the competitive digital age job market. The method utilized inthis study is descriptive with a qualitative research approach, with the primary objective of defining the students’ soft skills level. The Data respondent consisted of 8 students of the B and C Package Equivalence Education Program, one tutor, and one administrative staff at Al Ghofur Community Learning Center. Data are gathered and retrieved via questionnaires, interviews, and documentation studies. The findings indicate that students' soft skills for work preparedness are still lacking at AlGhofur Community Learning Center, resulting in students' readiness to enter the competitive digital age job market competition